2019
DOI: 10.1016/j.jallcom.2018.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible silica-based magnesium composites

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The observed peaks are in line with other work on sintered Mg-SiO 2 materials, with Mg 2 Si being present in mechanically alloyed [ 42 ] and/or sintered materials [ 43 ] within the previous works. In addition, the SiO 2 peak observed in Figure 12 b was also in line with nanosized SiO 2 in the literature [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The observed peaks are in line with other work on sintered Mg-SiO 2 materials, with Mg 2 Si being present in mechanically alloyed [ 42 ] and/or sintered materials [ 43 ] within the previous works. In addition, the SiO 2 peak observed in Figure 12 b was also in line with nanosized SiO 2 in the literature [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…It could be found that the degradation rates of the Fe/Mg 2 Si composites (0.15 ± 0.013, 0.21 ± 0.015, 0.31 ± 0.021, and 0.33 ± 0.030 mm/y for Fe/0.3Mg 2 Si, Fe/0.6Mg 2 Si, Fe/0.9Mg 2 Si, and Fe/1.2Mg 2 Si, respectively) were obviously higher than that of Fe (0.12 ± 0.011 mm/y) and the degradation rate increased with the increasing content of Mg 2 Si in the composites. This trend was explained by the decomposition of Mg 2 Si in the SBF through a chemical reaction with H 2 O[ 45 , 46 ]. It should be stated that the degradation rates of Fe/0.9Mg 2 Si and Fe/1.2Mg 2 Si composites were among 0.2 – 0.5 mm/y, which was a suitable degradation rate to match the restoration process of new bone[ 2 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that PBS has been extensively used as the corrosion testing medium of Mg and its alloys [61][62][63][64], it is not generally a suitable solution to simulate or predict the in vivo degradation behavior of Mg, since phosphate with Mg 2+ can create insoluble precipitation on the surface of the metal, which can produce inaccurate results [53,65]. Mena-Morcillo et al [66] investigated the degradation of AZ31 and AZ91 Mg alloys in SBF, Hanks', and Ringer's solutions.…”
Section: Mg Corrosion In Simulated Body Environmentsmentioning
confidence: 99%